The impact of combined decaffeinated green coffee and green tea, metformin, and empagliflozin on SAMD11 mRNA expression in vascular calcification associated with metabolic syndrome in Sprague Dawley rats - Taufiq, Fikri; Saifur Rohman, Mohammad; Fuji Rahimah, Anna (Heart Science Journal, 2026)
Background: Vascular calcification, a common complication of metabolic syndrome, increases cardiovascular risk, and SAMD11 may be implicated in its development. Improving blood glucose with metformin, empagliflozin or a combination of decaffeinated green tea and green coffee may improve metabolic syndrome which may ultimately lead to SAMD11 expression. However, the precise mechanisms by which SAMD11 play a role on vascular calcification in metabolic syndrome remain unknown. Objective: This study investigated the effect of combined decaffeinated green coffee and green tea, metformin and empagliflozin on SAMD11 mRNA expression in metabolic syndrome-induced vascular calcification. Methods: Twenty-five 12-week-old male Sprague Dawley (SD) rats were randomly assigned to five groups: control, metabolic syndrome (MetS), combine decaffeinated green tea 300 mg/kgBW and green coffee 200 mg/KgBW treatment, metformin 500 mg/kgBW treatment, and empagliflozin 30 mg/KgBW treatment. MetS was induced using established procedures. Vascular calcification and aortic SAMD11 mRNA expression were assessed via HE staining and RT-PCR, respectively. Result: Induction of metabolic syndrome in SD rats successfully led to vascular calcification. Metabolic syndrome induction significantly increased SAMD11 mRNA expression (p=0.018), an effect that was reversed by treatment with metformin (p=0.002) and empagliflozin (p=0.005). While a combination of decaffeinated green tea and green coffee showed a reduction in SAMD11 mRNA expression, but this reduction was not statistically significant (p=0.066). Conclusion: Metabolic syndrome may promote vascular calcification by enhancing SAMD11 mRNA expression. Controlling hyperglycaemia, a characteristic of metabolic syndrome, with metformin and empagliflozin, reduced SAMD11 mRNA expression. Potential hyperglycaemic control by decaffeinated green tea and green coffee did not changes SAMD11 mRNA expression.